EXPERIMENTAL STUDY ON OTTO ENGINE PERFORMANCE WITH VARIATIONS IN COMPRESSION RATIO AND GASOLINE OCTANE - Bahtiar Rahmat; Irwan Setyo Prabowo; Yuris Bahadur Wirawan; Fahmy Zuhda Bahtiar (Otopro, 2026)
This research aims to analyze the effect of compression ratio variation and gasoline octane number on the performance of spark-ignition internal combustion engines. The experimental object was a single-cylinder 124 cc motorcycle engine with an original compression ratio of 9.6:1. The compression ratio was increased to 10.6:1 by reducing the cylinder height by 0.6 mm. Performance testing was carried out using a dynamometer with two types of fuel, RON 88 and RON 92. Octane number 92 was selected based on fuel availability, while octane number 88 was used to evaluate engine performance under an increased compression ratio. A cylinder wall length reduction of 0.6 mm was applied as the maximum allowable limit, beyond which cylinder head modification would be required. The performance parameters evaluated were torque and brake power over an engine speed range of 4000–7000 rpm. The results indicate that increasing the compression ratio from 9.6:1 to 10.6:1 improved engine torque and brake power by approximately 3.8% to 4%. Meanwhile, the use of higher-octane gasoline (RON 92) increased performance by only about 2% to 2.4%, and only when used in the higher compression engine. In contrast, using high-octane fuel in a low-compression engine resulted in reduced performance due to ignition delay. Overall, the optimal performance was achieved when a high compression ratio was paired with high-octane fuel. Therefore, selecting an appropriate octane rating according to the engine compression ratio is essential to achieve optimal combustion efficiency, brake power output, and torque response.